New approach to the efficiency increase problem for multi-junction silicon photovoltaic converters with vertical diode cells - Kopach, V. R.; Kirichenko, M. V.; Shramko, S. V.; Zaitsev, R. V.; Bondarenko, S. A. (Scientific and Technological Corporation "Institute for Single Crystals", 2008)
It is shown, that for efficiency increase of multi-junction photovoltaic solar energy converters with vertical diode cells (VDC) on the basis of single-crystal silicon the modernization of VDC by the introduction along their vertical Si-boundaries single-layer indiumtin oxide reflectors by thickness more than 1 μm is necessary.

Показано, що для підвищення ККД багатоперехідних фотоелектричних перетворювачів сонячної енергії з вертикальними діодними комірками (ВДК) на основі монокристалічного кремнію необхідна модернізація ВДК шляхом введення уздовж їх вертикальних Sі-границь одношарових рефлекторів з індій-олов'яного оксиду товщиною більше 1 мкм.
Новий підхід до проблеми підвищення ККД багатоперехідних кремнієвих фотоелектричних перетворювачів з вертикальними діодними комірками
Keywords: photovoltaic solar energy converters; vertical diode cells; electrical power; chemical reactions; коефіцієнт корисної дії; сонячна енергія; електрична енергія; хімічні реакції; монокристалічний кремній; рефлектори